2023
DOI: 10.3389/fmars.2023.997491
|View full text |Cite
|
Sign up to set email alerts
|

A review of post-whaling abundance, trends, changes in distribution and migration patterns, and supplementary feeding of Southern Hemisphere humpback whales

Elisa Seyboth,
Jan-Olaf Meynecke,
Jasper de Bie
et al.

Abstract: Southern Hemisphere humpback whales (Megaptera novaeangliae) were heavily targeted during modern commercial whaling operations, with some 216,000 individuals killed between 1903 and 1973. That impacted the abundance of all the seven breeding stocks of the species. Most of these stocks have been recovering from whaling pressure although the understanding of the current growth rates of some stocks, and how the rates compare across stocks are lacking. Updated information is fundamental for understanding the speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 200 publications
1
2
0
Order By: Relevance
“…Therefore, our results probably reflect the abundance of humpback whales migrating to the western part (i.e., including mostly the South Atlantic and Pacific breeding populations) of the Southern Ocean. Recent estimates arrived at an abundance estimate of 47,119 humpback whales in the western part of the Southern Ocean (Seyboth et al, 2023), which corresponds to 61% of the pre-whaling abundance estimate obtained here. Using the growth rate estimated by Zerbini and colleagues (2019) for this region at 7% would imply that this population could be at pre-whaling abundance by 2045.…”
Section: Pre-and Post-whaling Abundancesupporting
confidence: 57%
See 2 more Smart Citations
“…Therefore, our results probably reflect the abundance of humpback whales migrating to the western part (i.e., including mostly the South Atlantic and Pacific breeding populations) of the Southern Ocean. Recent estimates arrived at an abundance estimate of 47,119 humpback whales in the western part of the Southern Ocean (Seyboth et al, 2023), which corresponds to 61% of the pre-whaling abundance estimate obtained here. Using the growth rate estimated by Zerbini and colleagues (2019) for this region at 7% would imply that this population could be at pre-whaling abundance by 2045.…”
Section: Pre-and Post-whaling Abundancesupporting
confidence: 57%
“…Estimates of pre-whaling humpback whale abundance in the Southeast Pacific are scarce, but a few assessments were performed based on catch records and recent abundance surveys (Félix et al, 2020;Warwick-Evans et al, 2022), which suggested a pre-whaling abundance at ~22,000, some three times lower than the genome-based estimates. Given recent post-whaling population surveys in the Southeast Pacific (Seyboth et al, 2023;Warwick-Evans et al, 2022) and a population annual growth rate of 5.5% (Félix et al, 2020), our findings suggest that the Southeast Pacific humpback whales would be currently at ~16% of their pre-whaling numbers and will likely reach pre-whaling levels only by 2056.…”
Section: Pre-and Post-whaling Abundancementioning
confidence: 73%
See 1 more Smart Citation